Genetic variation of Phoma sorghina isolates from Southern Africa and Texas - Pažoutová, Sylvie (Folia microbiologica, 2009)
Genetic variability of Phoma sorghina, a ubiquitous facultative phytopathogen, was investigated on 41 isolates cultivated from surface-sterilized sorghum grains originating from South Africa and Texas; pearl millet isolates from Namibia were also included. Most of the isolates from Texas produced intense red pigments, especially on Czapek-Dox agar plates. Many African isolates formed conspicuous dark radial substrate hyphae with intercalated chlamydospores on oatmeal plates. Conidial dimensions and shape were very variable (mean lengths 4.5-5.7 microm). Haplotypes were defined based on 53 markers from banding patterns obtained with rep-PCR (primers: M13core, ERIC IR). The shared geographic origin was partially reflected in the clades of the haplotype phylogram. The values of G(ST) were intermediate; 16-37 % of the variation was found between the populations. Nm values of gene flow were 0.84-1.15. Average gene diversity H(E) was moderate (0.256). Sequences of ITS-rDNA were obtained from 21 isolates. Allele 1 was found in 9 isolates scattered throughout the clades, allele 2 occurred in 6 isolates (5 of them from the same clade), alleles 3 and 4 were shared by two isolates each and two isolates were unique. Alleles 1 and 2 were also found among highly related sequences from GenBank. All shared an 8-bp deletion near the 5' end of ITS2 that was not found in any other Phoma/Didymella species and which may be a typical marker for P. sorghina. Among related species, members of legume-associated Ascochyta/Didymella complex, Epicoccum spp., D. applanata and P. glomerata were found.
Keywords: financování organizované; Ascomycota; ribozomální DNA; Edible Grain; DNA, Ribosomal; jedlá semena; South Africa; Molecular Sequence Data; DNA, Fungal; Sorghum; mezerníky ribozomální DNA; Genetic Variation; Phylogeny; Jihoafrická republika; Financing, Organized; Texas; molekulární sekvence - údaje; alely; DNA fungální; Alleles; DNA, Ribosomal Spacer; fylogeneze; genetická variace